Long-term low-dose alcohol intake promotes white adipose tissue browning and reduces obesity in mice. Issue 16 (26th July 2022) - Xuan, Xiuchen; Tan, Peizhu; Zhang, Ximei; Huang, Hui; Li, Yanze; Jiang, Yu; Yu, Aimiao; Zhao, Yuanyuan; Wang, Kuo; Tang, Baozhu; Qu, Shuye; Jiang, Yunyan; et al.
Abstract : There are numerous pieces of evidence indicating that moderate alcohol intake has a protective effect on metabolic diseases. Abstract : There are numerous pieces of evidence indicating that moderate alcohol intake has a protective effect on metabolic diseases. Our previous studies revealed that long-term low-dose alcohol intake resists high-fat diet (HFD) induced obesity. A process in which white adipose tissue can be stimulated and turned into heat-producing brown adipose tissue named white adipose browning is associated with energy expenditure and weight loss. In this study we aimed to investigate whether alcohol causes the browning of white adipose tissue and whether the browning of white adipose tissue is involved in the resistance to the occurrence of obesity caused by long-term low-dose alcohol intake. After eight months of alcohol feeding, the body weight of mice had no significant change, but the fat content and lipid deposition in the liver were reduced. Morphological observations revealed that the browning of white adipose tissue occurred. The white adipose tissue browning marker UCP1 gene and protein expression levels were increased and the expression of the PGC1-α/PPAR-α pathway protein and the P38 MAPK/CREB pathway protein was also elevated in the alcohol feeding group. Moderate alcohol drinking increased the secretion of the CXCL14 protein in inguinal subcutaneous adipose tissue, which drove the recruitment of M2 macrophages. Moderate alcohol drinking mice had faster lipid metabolism and slower lipid anabolism. In addition, we found that long-term low-dose alcohol intake prevented the increase of body weight, triglycerides, inflammation and energy expenditure decrease induced by HFD. Moderate alcohol consumption increased the expression of UCP1 and glucose uptake in the adipose tissue of the HFD group. In conclusion, our results show for the first time that alcohol can trigger the browning of white adipose tissue to counteract obesity.